Identifying the global transmission of the 2007-09 financial crisis in a GVAR Model - Alexander Chudik; Marcel Fratzscher (European Central Bank (ECB), 2011)
The paper analyses and compares the role that the tightening in liquidity conditions and the collapse in risk appetite played for the global transmission of the financial crisis. Dealing with identification and the large dimensionality of the empirical exercise with a Global VAR approach, the findings highlight the diversity of the transmission process. While liquidity shocks have had a more severe impact on advanced economies, it was mainly the decline in risk appetite that affected emerging market economies. The tightening of financial conditions was a key transmission channel for advanced economies, whereas for emerging markets it was mainly the real side of the economy that suffered. Moreover, there are some striking differences also within types of economies, with Europe being more adversely affected by the fall in risk appetite than other advanced economies.
Keywords: E44; F3; C5; 330; advanced economies; Emerging market economies; financial crisis; global transmission; Global VAR (GVAR); liquidity; modelling; risk; shocks; US